Information Shocks, Liquidity Shocks, Jumps, and Price Discovery: Evidence from the U.S. Treasury Market - Jiang, George J.; Lo, Ingrid; Verdelhan, Adrien (Journal of Financial and Quantitative Analysis, 2011)
Abstract In this paper, we identify jumps in U.S. Treasury-bond (T-bond) prices and investigate what causes such unexpected large price changes. In particular, we examine the relative importance of macroeconomic news announcements versus variation in market liquidity in explaining the observed jumps in the U.S. Treasury market. We show that while jumps occur mostly at prescheduled macroeconomic announcement times, announcement surprises have limited power in explaining bond price jumps. Our analysis further shows that preannouncement liquidity shocks, such as changes in the bid-ask spread and market depth, have significant predictive power for jumps. The predictive power is significant even after controlling for information shocks. Finally, we present evidence that post-jump order flow is less informative relative to the case where there is no jump at announcement.